The Dark and Light Sides of Empathy: The Clinical Relevance of the Assessment of Cognitive and Affective Empathy Across Negative and Positive Emotions - Paweł Larionow (European Journal of Investigation in Health, Psychology and Education)
Is empathy a “double-edged sword”? This study aimed to contribute to a more nuanced understanding of the multidimensional empathy construct in the statistical prediction of negative and positive mental health outcomes. More specifically, this research intended to reveal whether, what, and how four individual empathy dimensions (i.e., cognitive empathy for negative emotions, cognitive empathy for positive emotions, affective empathy for negative emotions, and affective empathy for positive emotions) uniquely statistically predicted the levels of anxiety and depression symptoms, as well as well-being. A total of 786 Polish-speaking adults (452 females and 334 males) filled out a series of self-report questionnaires on empathy (the Perth Empathy Scale), anxiety, and depression symptoms, as well as well-being. Adjusting for demographic variables, the frequentist and Bayesian multiple regression analyses revealed that affective empathy dimensions (i.e., abilities to vicariously share others’ emotions) significantly predicted psychopathology symptoms and well-being, whereas cognitive empathy dimensions (i.e., abilities to understand others’ emotions) did not. In particular, higher affective empathy for negative emotions contributed to worse mental health outcomes, whereas higher affective empathy for positive emotions contributed to better mental outcomes. Overall, the results indicated that individual empathy dimensions demonstrated their specific dark and light sides in the statistical prediction of mental illness and well-being indicators, further supporting the clinical relevance of the multidimensional empathy construct.